To find the equation that models the linear relationship given the table of values, we can first determine the slope (\(m\)) and the y-intercept (\(b\)) of the linear equation in slope-intercept form, which is \(y = mx + b\).
Given the points from the table:
- (-2, -7)
- (0, -3)
- (2, 1)
- (4, 5)
- Calculate the slope (\(m\)):
Using the formula: \[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
We can choose any two points. Let’s use (0, -3) and (2, 1): \[ m = \frac{1 - (-3)}{2 - 0} = \frac{1 + 3}{2} = \frac{4}{2} = 2 \]
- Determine the y-intercept (\(b\)):
Using the slope and one of the points (we can use (0, -3)): \[ y = mx + b \implies -3 = 2(0) + b \implies b = -3 \]
- Equation of the line:
Now that we have \(m = 2\) and \(b = -3\), we can write the equation: \[ y = 2x - 3 \]
Thus, the equation that models this relationship in slope-intercept form is:
y = 2x − 3
So the correct response is: y = 2x − 3